Transferability of green port strategies: A Delphi study with European ports - Aren Bostooughli; Adriana Saraceni (Journal of International Maritime Safety, Environmental Affairs, and Shipping)
This research aims to identify suitable green port strategies for small EU ports, by first examining green port strategies of leading European ports and then their applicability in the context of small ports, by assessing challenges and barriers encountered during strategy implementation. Several port environmental issues were identified, including 12 green port strategies and their corresponding port emission areas. Two rounds of a Delphi study, namely a survey and semi-structured validation interviews were conducted with 21 experts from four European ports, to understand port characteristics, examine the applicability of the strategies, and identify challenges and barriers associated with their implementation. In total, six strategies are deemed suitable for application in small ports, specifically renewable energy, clean power vehicles, waste management, slow steaming, modal shifting, and incentives for green trucks. By identifying green port strategies applicable to small ports, based on small port characteristics and implementation challenges arising from these, this research addresses a gap in academic literature. We provide small port management and relevant stakeholders with a list of applicable innovations and growth policies essential for achieving green port status.